2015
DOI: 10.1016/j.ajem.2015.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital recognition of severe sepsis: development and validation of a novel EMS screening tool

Abstract: Objective-To derive and validate a predictive model and novel Emergency Medical Services (EMS) screening tool for severe sepsis (SS). Design-Retrospective cohort study.Setting-A single EMS system and an urban, public hospital.Patients-Sequential adult, non-trauma, non-arrest, at-risk, EMS-transported patients between January 1, 2011 and December 31, 2012. At-risk patients were defined as having all 3 of the following criteria present in the EMS setting: heart rate >90bpm, 2) respiratory rate >20bpm, and 3) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“… 29–31 Six studies addressed the identification of sepsis within EMS. 12 15 20 21 27 28 Collectively, six prehospital screening tools were identified in the course of the review (critical illness score, 32 Prehospital Recognition of Severe Sepsis (PRESS) score, 31 Prehospital Early Sepsis Detection (PRESEP) score, 30 Robson tool, 21 30 modified Robson tool 15 and BAS 90-30-90 21 30 ); a single study reported the accuracy of the Modified Early Warning Score (MEWS). 30 None of the studies were prospective and no studies were designed specifically to validate a prehospital sepsis screening tool in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“… 29–31 Six studies addressed the identification of sepsis within EMS. 12 15 20 21 27 28 Collectively, six prehospital screening tools were identified in the course of the review (critical illness score, 32 Prehospital Recognition of Severe Sepsis (PRESS) score, 31 Prehospital Early Sepsis Detection (PRESEP) score, 30 Robson tool, 21 30 modified Robson tool 15 and BAS 90-30-90 21 30 ); a single study reported the accuracy of the Modified Early Warning Score (MEWS). 30 None of the studies were prospective and no studies were designed specifically to validate a prehospital sepsis screening tool in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…There are limited reports of validated screening tools for recognition of sepsis in the prehospital setting. One tool recently developed and validated is the prehospital severe sepsis (PRESS) screening tool which involves a score calculated from EMS data on 6 risk factors [ 15 ]. Using the PRESS tool in the setting of an urban public hospital, prehospital recognition of severe sepsis by EMS staff had a sensitivity of 86% and a specificity of 47% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…One tool recently developed and validated is the prehospital severe sepsis (PRESS) screening tool which involves a score calculated from EMS data on 6 risk factors [ 15 ]. Using the PRESS tool in the setting of an urban public hospital, prehospital recognition of severe sepsis by EMS staff had a sensitivity of 86% and a specificity of 47% [ 15 ]. The Sepsis Alert Protocol is another screening tool for EMS providers and was found to accurately identify severe sepsis in 47.8% of cases in a pilot study [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should not be limited to the ICU but include the emergency department and the wards (and potentially both pre-hospital emergency care and outpatient facilities for sepsis screening as well) [122,123]. These can be intra-location delivery systems (i.e.…”
Section: Administration/epidemiologymentioning
confidence: 99%